Pengaruh Metode Penugasan dan Presentasi terhadap Prestasi Akademik Mahasiswa : The Influence of Assignment and Presentation Methods on Students' Academic Achievement - Abdul Jabar Idharudin; Muwahidah Nurhasanah; Samsuddin, Samsuddin (TARBIYAH: Jurnal Pendidikan dan Pembelajaran, 2025)
This research aims to analyze the influence of assignment and presentation methods on academic achievement. This research uses a quantitative descriptive method with data collection through questionnaires and inferential statistical analysis of 2 predictor regressions. The research results show that there is a significant influence between assignment and presentation methods on academic achievement. There is a significant influence between assignment method (X1) and academic achievement (y). Each improvement in assignment method correlates with a 0.5 unit increase in academic achievement. Improving the quality of assignment methods contributes positively to increasing academic achievement. There is a significant influence between presentation (X2) and academic achievement (y). Each increase in presentation was positively correlated with a 0.7 unit increase in academic achievement. Assignment and presentation methods contributed 63.4% to the variance in academic achievement (R Squared = 0.634). This shows that the use of these two variables in the regression model increases the ability to explain variations in academic achievement. The findings of this research show that assignment and presentation methods have a significant influence, so they have an important role in improving academic achievement for students of the PAI STAI Al-Hidayah Bogor scholarship program. The implications of this research are for educational institutions to pay attention to the quality of assignment and presentation methods as learning strategies to improve student academic achievement.